Structural, Morphological, and Magnetic Properties of Nickel Substituted Cobalt Zinc Nanoferrites at Different Sintering Temperature (Journal of Nepal Physical Society, 2021)
Co-precipitation was used for the preparation of Co0.5-xNixZn0.5Fe2O4 (x = 0 to 0.3) nanoferrites. The inverse spinel structure of the samples was clearly shown by the structural analysis of X-ray Diffractometer (XRD) and Fourier Transform Infrared (FTIR) Spectroscopy. We have studied the effect of sintering temperature (500oC) on the lattice constant and particle size using XRD. The average lattice parameters for the non-sintered and sintered samples were 8.377 Å and 8.354 Å respectively. For the non-sintered sample, the nickel concentration decreases the lattice parameter from 8.354 Å to 8.310 Å due to its smaller ionic radii than that of cobalt. While for a sintered sample at 500oC, the lattice parameter increases for concentration x=0.3 due to the thermal effect. The particle size calculated by Transmission Electron Microscope (TEM) agrees well with that of XRD. The morphological and compositional analysis was done with the help of Scanning Electron Microscopy (SEM) and the attached Energy Dispersive X-ray (EDX) Analyzer. The increasing percentage of nickel with decreasing percentage of cobalt shows that the cobalt is substituted by Nickel. The magnetic properties were studied by Vibrational Spectrometer (VSM). The value of saturation magnetization is higher for x=0.1 but lower for x=0.2 and 0.3 due to their particle size. The hysteresis loop of the samples their superparamagnetic behavior at room temperature.